Application of Chebyshev Polynomials to the Approximate Solution of Singular Integral Equations of the First Kind with Cauchy Kernel on the Real Half-line - Shali, J. Ahmadi; Akbarfam, A. Jodayree; Kashfi, M. (Communications in Mathematics and Applications, 2013)
In this paper, exact solution of the characteristic equation with Cauchy kernel on the real half-line is presented. Next, the Chebyshev polynomials of the second kind, U_n(x), and fourth kind, W_n(x), are used to derive numerical solutions of Cauchy-type singular integral equations of the first kind on the real half-line. The collocation points are chosen as the zeros of the Chebyshev polynomials of the first kind, T_n+2(x), and third kind, V_n+1(x). Moreover, estimations of errors of the approximated solutions are presented. The numerical results are given to show the accuracy of the methods presented.